The Bloomsbury Encyclopedia of Film and Television Costume Design - Landis, Deborah Nadoolman 1952- (Bloomsbury Visual Arts, 2023)
The Bloomsbury Encyclopedia of Film and Television Costume Design is the first reference work on costume for screen. Genuinely global in scope, and comprising 3 volumes and over 800,000 words, the work encompasses designers for film and television productions from America, Europe, Asia, Africa, Latin America and beyond, from early cinema to the present day. This highly illustrated work includes articles from a wide range of practitioners and scholars spanning film studies, fashion theory and costume history. In addition to original overview articles on genres, regions and individual designers, the work includes single costume case studies analysing the contribution of distinguished costume designers and key costumes significant to international popular culture and the history of film and television. Examining the process of costume design from script to screen, by genre and by region, and the centrality of the designer, this authoritative work is the ultimate reference on costume design for film and television